Preparation method of low-cost long-cycle lithium iron phosphate positive electrode material
By using ferrous octahydrate ferrous phosphate and industrial grade lithium carbonate as raw materials, combined with spray drying and airflow crushing and grading processes, the problems of high cost and low firing rate in the existing lithium iron phosphate production process are solved, and the low-cost and high-efficiency preparation of lithium iron phosphate positive electrode material is achieved, and the sintering performance and discharge capacity of the material are improved.
Patent Information
- Application Number
- CN202510188982.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-06-03
AI Technical Summary
The existing lithium iron phosphate production process has problems with high cost and low firing rate, especially in the sintering process in the ferrous oxalate process, which leads to high costs.
The low-cost ferrous phosphate octahydrate is used as raw material, and the precipitation is prepared by the by-product ferrous sulfate produced by titanium dioxide, combined with industrial-grade lithium carbonate for precipitation, and spray drying and airflow pulverization and grading processes are used to perform primary and secondary grinding, and sintering is carried out through a kiln to control the sintering temperature and cycle to improve the sintering rate.
The production of long-circulated lithium iron phosphate positive electrode materials at low cost and high efficiency has been achieved, reducing the cost of raw materials and equipment, and improving the sintering performance and discharge capacity of the materials.
Smart Images

Figure CN120081352A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery material preparation, and specifically to a preparation method of a low-cost and long-cycle lithium iron phosphate cathode material. Background Art
[0002] With the intensification of competition in the lithium iron phosphate industry, cost reduction and efficiency improvement have become an important part of technological improvement. The current mainstream solid-phase methods for producing lithium iron phosphate are mainly the iron phosphate process and the ferrous oxalate process. The iron phosphate process uses iron phosphate and lithium carbonate to synthesize lithium iron phosphate, which has high performance requirements for iron phosphate, and the incomplete reduction of trivalent iron will affect the capacity of lithium iron phosphate during the preparation process. The ferrous oxalate process has better product performance, but a large amount of water and carbon dioxide are generated during the sintering process, resulting in a low firing rate and high costs. Summary of the Invention
[0003] The purpose of the present invention is to provide a preparation method of a low-cost and long-cycle lithium iron phosphate cathode material to solve the problems mentioned in the background art.
[0004] To achieve the above purpose, the present invention provides the following technical solutions:
[0005] A preparation method of a low-cost and long-cycle lithium iron phosphate cathode material, comprising the following steps:
[0006] The first step: Put Li 3 PO 4 , Fe 3 (PO 4 ) 2 ·8H 2 O, a carbon source, and an additive into a sand mill for primary grinding until the particle size is less than 5 μm, then enter secondary grinding, and after grinding to a particle size less than 1 μm, perform spray drying;
[0007] The second step: After the spray material produced by spray drying is loaded into a sagger, after vibration, degassing and pressurization, enter a kiln for calcination;
[0008] The third step: After the spray material is calcined and taken out of the kiln, perform air flow crushing and classification to obtain the lithium iron phosphate cathode material.
[0009] In one embodiment, the synthesis raw materials of the Li 3 PO 4 are industrial-grade lithium carbonate, hydrochloric acid, and phosphoric acid. After dissolving lithium carbonate in hydrochloric acid, use phosphoric acid to precipitate to obtain the Li 3 PO 4 ; the content of dry-base Li 2 CO 3 in the industrial-grade lithium carbonate is > 98%.
[0010] In one embodiment, the Fe 3 (PO 4 ) 2 ·8H 2 O is specifically prepared by adjusting the pH of the by-product ferrous sulfate solution of titanium dioxide to the range of 4 to 6 with ammonia water, NaOH, citric acid, acetic acid, and sodium dihydrogen phosphate solution, and then adding phosphoric acid. At a certain temperature and stirring speed, Fe 3 (PO 4 ) 2 ·8H 2 O precipitate is formed.
[0011] In one embodiment, the stirring temperature is 70 to 80 °C and the pH is 5 to 6.
[0012] In one embodiment, the carbon source is one or more of glucose, fructose, citric acid, sucrose, polyvinyl alcohol, polyethylene glycol 6000 - 10000, stearic acid, and paraffin, and the additive is one or more of MnO 2 , TiO 2 , MgO, NiO 2 , V 2 O 5 .
[0013] In one embodiment, the degassing pressure is 5000 - 10000 Pa, the airflow crushing pressure is 300 - 400 Pa, and the D50 of the classified powder is 0.5 - 0.9 μm.
[0014] In one embodiment, the spray drying temperature is 60 - 65 °C, and the whole process from spray drying to sintering operation is protected by nitrogen.
[0015] In one embodiment, the grinding medium in the grinding operation is methanol or ethanol. The grinding operation adopts two-stage ball milling. In the first-stage sand mill, the diameter of the zirconia balls used is 1.8 - 2.0 mm. After grinding to a particle size < 5 μm, it is put into the second-stage sand mill, and the diameter of the zirconia balls used is 0.8 - 1.0 mm. After grinding to a particle size < 1 μm, spray drying is carried out.
[0016] In one embodiment, the kiln includes a roller hearth kiln and a rotary kiln;
[0017] Among them, when using the roller hearth kiln, after the powder is vibration degassed, the powder in the sagger is compacted by a mold press and then enters the roller hearth kiln. The sintering temperature is 760 to 810 °C, and the sintering cycle is 20 - 24 h;
[0018] When using a rotary kiln, after the powder undergoes vibration degassing, it enters a double-roll granulator for pressing to compact the powder, and is directly conveyed into the rotary kiln. The sintering temperature is 740 - 790 °C, and the sintering cycle is 18 - 22 h.
[0019] In one of the embodiments, the Li 3 PO 4 and Fe 3 (PO 4 ) 2 ·8H 2 O is prepared according to the molar ratio of Li:Fe:P of 1:1:1.
[0020] Compared with the prior art, the present invention has the following advantages or beneficial effects:
[0021] By using ferrous phosphate octahydrate in the present invention, which is prepared by precipitating ferrous sulfate, a by-product of titanium dioxide production, the resources are effectively utilized and the cost is reduced;
[0022] Secondly, lithium phosphate therein is prepared by precipitating with industrial-grade lithium carbonate, and the cost of Li is also lower than that of battery-grade lithium carbonate, achieving cost reduction and efficiency improvement;
[0023] Finally, the synthesis of the technical route of the present invention is a solid solution reaction between the main materials, and the material firing yield > 75%, so the cost advantage is obvious. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is the XRD test diagram of Example 1 in the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0026] Example 1
[0027] (1) Li 3 PO 4 , Fe 3 (PO 4 ) 2 ·8H 2 O are prepared according to the molar ratio of Li:Fe:P of 1:1:1, and Li 3 PO 4 and Fe 3 (PO 4 ) 2 ·8H 21% glucose, 4% polyethylene glycol 10000, 0.5% paraffin wax and 0.1% TiO by mass of O 2 They are put into a first-stage sand mill together, using methanol as the grinding medium, adding a methanol solution according to a mass ratio of 1:1 of substances. The diameter of the zirconia balls used in the first-stage sand mill is 1.8 - 2.0 mm, 500 kg of zirconia balls are added, the sand mill rotates at 600 rpm, and after grinding for 30 min until the particle size is < 5 μm, it is put into a second-stage sand mill. The diameter of the zirconia balls used is controlled to be 0.8 - 1.0 mm, the addition amount is 500 kg, the rotation speed is 650 rpm, and 20% of the methanol by mass of the substances is added again. After grinding for 2 h until the particle size is < 1 μm, spray drying is carried out, and the spray drying temperature is 60 °C.
[0028] (2) The powder after spray drying enters a graphite crucible through an automatic potting machine, then enters a compaction bin for compaction, and then enters a pressurization bin. The pressure plate in the pressurization bin compresses the powder at a pressure of 5000 Pa while pumping air, and then enters the kiln for sintering; according to the size and length of the kiln, it is preferably to use 780 - 800 °C as the sintering temperature, the sintering cycle is 22 h. After sintering is completed, airflow crushing and classification are used to crush the material to 0.5 - 0.9 μm to obtain the lithium iron phosphate cathode material. As shown in XRD Figure 1 , it can be seen that the peak pattern is standard, there are no impurity peaks, and the crystallinity is high; in the coin cell test, the tap density of 3 tons of the powder reaches 2.58, and the discharge capacity at 0.1C > 158 mAh / g.
[0029] Example 2
[0030] (1) Li 3 PO 4 , Fe 3 (PO 4 ) 2 ·8H 2 O are prepared according to a molar ratio of Li:Fe:P of 1:1:1, adding 1% glucose, 4% polyethylene glycol 10000, 0.5% paraffin wax and 0.1% TiO by mass of Li 3 PO 4 and Fe 3 (PO 4 ) 2 ·8H 2 O 2Put them together into a first-stage sand mill, using methanol as the grinding medium, adding a methanol solution in a mass ratio of 1:1. The diameter of the zirconia balls used in the first-stage sand mill is 1.8 - 2.0 mm. Add 500 kg of zirconia balls, the rotational speed of the sand mill is 600 rpm. After grinding for 30 min until the particle size is < 5 μm, put it into a second-stage sand mill. Control the diameter of the zirconia balls used to be 0.8 - 1.0 mm, the addition amount is 500 kg, the rotational speed is 650 rpm. Add methanol accounting for 20% of the mass of the substance again, grind for 2 h until the particle size is < 1 μm, and then carry out spray drying, and the spray drying temperature is 60 °C.
[0031] (2) The powder after spray drying enters the front bin. After 3 min of vibration degassing, it enters a double-roll granulator. The powder is kneaded and granulated under a pressure of 10 kg, and then enters a rotary kiln for sintering. Use 770 - 780 °C as the sintering temperature, the sintering cycle is 20 h. After sintering is completed, use air-flow crushing and classification to crush the material to 0.5 - 0.9 μm to obtain the lithium iron phosphate cathode material.
[0032] Example 3
[0033] (1) Mix Li 3 PO 4 , Fe 3 (PO 4 ) 2 ·8H 2 O according to the molar ratio of Li:Fe:P of 1:1:1. Add glucose accounting for 1% of the mass of Li 3 PO 4 and Fe 3 (PO 4 ) 2 ·8H 2 O, polyethylene glycol 10000 accounting for 4%, paraffin wax accounting for 0.5%, TiO 2 accounting for 0.1% and V 2 O 5 accounting for 0.03% together into a first-stage sand mill, using methanol as the grinding medium, adding a methanol solution in a mass ratio of 1:1. The diameter of the zirconia balls used in the first-stage sand mill is 1.8 - 2.0 mm. Add 500 kg of zirconia balls, the rotational speed of the sand mill is 600 rpm. After grinding for 30 min until the particle size is < 5 μm, put it into a second-stage sand mill. Control the diameter of the zirconia balls used to be 0.8 - 1.0 mm, the addition amount is 500 kg, the rotational speed is 650 rpm. Add methanol accounting for 20% of the mass of the substance again, grind for 2 h until the particle size is < 1 μm, and then carry out spray drying, and the spray drying temperature is 60 °C.
[0034] (2) The powder after spray drying enters a graphite sagger through an automatic loader, and then enters a vibration chamber for vibration, and then enters a pressurizing chamber. The pressure plate in the pressurizing chamber presses the powder at a pressure of 5000Pa while evacuating air, and then enters a kiln for sintering. Depending on the size and length of the kiln, 780-800°C is preferably used as the sintering temperature, and the sintering cycle is 22 hours. After sintering, the material is crushed to 0.5-0.9 μm using airflow pulverization and classification to obtain lithium iron phosphate positive electrode material.
[0035] Comparative Example 1
[0036] (1) Li 3 PO 4 , Fe 3 (PO 4 ) 2 8H 2 O was prepared according to the molar ratio of Li:Fe:P of 1:1:1, and Li 3 PO 4 and Fe 3 (PO 4 ) 2 8H 2 O mass 1% glucose, 4% polyethylene glycol 10000, 0.5% paraffin and 0.1% TiO 2 Put them into a sand mill together, use methanol as the grinding medium, add methanol solution at a mass ratio of 1:1, wherein the diameter of the zirconium oxide balls used in the sand mill is 0.8-1.0 mm, add 500 kg of zirconium balls, the sand mill speed is 600 rpm, grind for 4 hours until the particle size is less than 1 μm, and spray dry, and the spray drying temperature is 60 ° C.
[0037] (2) The spray-dried powder is fed into a graphite crucible through an automatic hopper, and then into a roller kiln for sintering, with a sintering temperature of 780-800°C and a sintering cycle of 22 hours. After sintering, the material is crushed to 0.5-0.9 μm using airflow pulverization and classification to obtain lithium iron phosphate positive electrode material.
[0038] The XRD pattern of the lithium iron phosphate cathode material prepared in Example 1 is as follows: Figure 1 The performance comparison of lithium iron phosphate prepared in the embodiment and the comparative example is shown in the following table:
[0039] Sample 0.1C Discharge 0.5C Discharge 3T Compaction Density Example 1 158.2 143.4 2.572 Example 2 159.5 145.2 2.558 Example 3 159.7 146.5 2.564 Comparative Example 1 157.8 138.4 2.49
[0040] From the comparison between Example 1 and Comparative Example 1, it can be seen that the use of secondary grinding can effectively save ball milling time, and sintering after molding can effectively improve the sintering performance of the material, thereby greatly improving its compaction density and discharge capacity.
[0041] From the comparison between Example 1 and Example 2, it can be seen that using a rotary kiln can improve the discharge performance of the material, reduce the sintering temperature and sintering cycle. The reason is that the rotary kiln can improve the uniformity of material sintering. However, the compaction will decrease to a certain extent compared with the roller hearth kiln.
[0042] From Example 1 and Example 3, it can be seen that by doping different types of additives, the discharge performance of the material at high rates can be improved. Because the solid-phase reaction occurs during the sintering of Li 3 PO 4 and Fe 3 (PO 4 ) 2 ·8H 2 O. The sintered material has a relatively high compaction, but a low ion mobility, which needs to be improved by doping. This example only provides an illustration and does not represent the optimal doping scheme.
[0043] In terms of cost, in terms of equipment, compared with the traditional spray drying - sintering process, this patent requires about 5 - 10% of the cost investment. And the lithium discount in the raw material cost can save 5% of the raw material cost. Since the iron source uses the by-product of titanium dioxide, it saves 20% of the cost compared with the iron phosphate method. The cost per ton of the finished material can be reduced by 5 - 8%. From the current market environment, the cost of lithium iron phosphate is mainly the raw material cost. Therefore, this invention has a greater advantage in cost reduction and efficiency improvement compared with the existing technology.
[0044] The above shows and describes the basic principles, main features and advantages of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, it is intended to include all changes within the meaning and scope of the equivalent elements of the claims in the present invention.
[0045] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a low-cost long-cycle lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: Step 1: Put Li3PO4, Fe3(PO4)2·8H2O, carbon source and additives into a sand mill for primary grinding until the particle size is less than 5μm, then enter secondary grinding until the particle size is less than 1μm, and then spray dry; Step 2: The spray material produced after spray drying is loaded into the sagger, vibrated, degassed and pressurized, and then enters the kiln for calcination; Step 3: After the spray material is calcined and taken out of the kiln, it is crushed and classified by air flow to obtain lithium iron phosphate positive electrode material.
2. The method for preparing a low-cost long-cycle lithium iron phosphate positive electrode material according to claim 1, characterized in that: The synthetic raw materials of the Li3PO4 are industrial-grade lithium carbonate, hydrochloric acid and phosphoric acid. The lithium carbonate is dissolved in hydrochloric acid and then precipitated with phosphoric acid to obtain the Li3PO4. The dry-base Li2CO3 content in the industrial-grade lithium carbonate is greater than 98%.
3. The method for preparing a low-cost long-cycle lithium iron phosphate positive electrode material according to claim 1, characterized in that: The Fe3(PO4)2·8H2O is specifically prepared by adjusting the pH of the titanium dioxide byproduct ferrous sulfate solution to a range of 4 to 6 using ammonia water, NaOH, citric acid, acetic acid and sodium dihydrogen phosphate solution, and then adding phosphoric acid at a certain temperature and stirring speed to generate Fe3(PO4)2·8H2O precipitate.
4. The method for preparing a low-cost long-cycle lithium iron phosphate positive electrode material according to claim 3, characterized in that: The stirring temperature is 70-80°C and the pH is 5-6.
5. The method for preparing a low-cost long-cycle lithium iron phosphate positive electrode material according to claim 1, characterized in that: The carbon source is one or more of glucose, fructose, citric acid, sucrose, polyvinyl alcohol, polyethylene glycol 6000-10000, stearic acid, and paraffin; and the additive is one or more of MnO2, TiO2, MgO, NiO2, and V2O5.
6. The method for preparing a low-cost long-cycle lithium iron phosphate positive electrode material according to claim 1, characterized in that: The degassing pressure is 5000-10000Pa, the air flow crushing pressure is 300-400Pa, and the powder D50 after classification is 0.5-0.9μm.
7. The method for preparing a low-cost long-cycle lithium iron phosphate positive electrode material according to claim 1, characterized in that: The spray drying temperature is 60-65° C., and the entire process from spray drying to sintering is protected by nitrogen.
8. The method for preparing a low-cost long-cycle lithium iron phosphate positive electrode material according to claim 1, characterized in that: The grinding medium in the grinding operation is methanol or ethanol, and the grinding operation adopts a two-stage ball mill. The diameter of the zirconium oxide balls used in the first-stage sand mill is 1.8-2.0 mm. After grinding to a particle size of less than 5 μm, it is put into the second-stage sand mill. The diameter of the zirconium oxide balls used is 0.8-1.0 mm. After grinding to a particle size of less than 1 μm, it is spray-dried.
9. The method for preparing a low-cost long-cycle lithium iron phosphate positive electrode material according to claim 1, characterized in that: The kilns include roller kilns and rotary kilns; When using a roller kiln, the powder is vibrated and degassed, and then the powder in the sagger is compacted using a molding machine, and then enters the roller kiln. The sintering temperature is 760 to 810°C, and the sintering cycle is 20 to 24 hours. When using a rotary kiln, the powder is vibrated and degassed, then enters a double-roll granulator for pressurization. The powder is compacted and directly transported into the rotary kiln. The sintering temperature is 740-790°C, and the sintering cycle is 18-22 hours.
10. The method for preparing a low-cost long-cycle lithium iron phosphate positive electrode material according to claim 1, characterized in that: The Li3PO4 and Fe3(PO4)2·8H2O are prepared according to a molar ratio of Li:Fe:P of 1:1:1.
Citation Information
Cited By
Method for preparing carbon-coated lithium iron phosphate composite material by adopting ferrous phosphate octahydrate
CN120698435A